Effectiveness of self-managed oral anticoagulant therapy in patients with recurrent venous thromboembolism - Bjerregaard Larsen, Torben; Skjøth, Flemming; Lerkevang Grove, Erik; Brønnum Nielsen, Peter; Christensen, Thomas Decker (Thrombosis and Haemostasis, 2016)
Patient-self-management (PSM) of oral anticoagulant therapy (OAT) with vitamin K antagonists for venous thromboembolism (VTE) has demonstrated efficacy in randomised, controlled trials. The aim of this study was to evaluate the effectiveness of PSM of OAT in everyday clinical practice. Prospectively registered patient data were obtained from databases at two hospitals, and cross-linkage with national patient registries provided detailed information on comorbidities and events. Patients with VTE performing PSM affiliated to major PSM centres were included as cases (N=444). A control group of patients on conventional treatment was propensity score selected in a ratio of 1:5 (N=2220) within matched groups. The effectiveness and safety was estimated using recurrent VTE, major bleeding events and all-cause death as outcomes. We found a lower rate of recurrent VTE among PSM patients compared to the control group with a hazard ratio (HR) of 0.63; 95 % confidence interval (CI) 0.42–0.95, whereas no difference was seen with bleeding (HR: 0.95; 95 % CI 0.44–2.02). The risk of all-cause death was lower for PSM patients (HR: 0.41; 95 % CI 0.21–0.81). A net clinical benefit analysis sums the effect on recurrent VTE and bleeding up to a weighted rate difference of 0.86 (95 % CI 0.00–1.72) in favour of PSM. In conclusion, PSM of anticoagulant treatment was associated with a statistically significant lower rate of recurrent VTE and all-cause death compared to patients on conventionally managed anticoagulant treatment. All major thromboembolic outcomes were less frequent among self-managed patients, whereas bleedings were observed with similar frequency.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Deep-vein thrombosis; anticoagulation treatment; pulmonary embolism; self-management